Care experiences of young people with eating disorders and their parents: a qualitative study. (23rd February 2017) - Mitrofan, Oana; Ford, Tamsin; Byford, Sarah; Nicholls, Dasha; Petkova, Hristina; Kelly, Jonathan; Edwards, Eve
Abstract: Background: In the UK, young people with eating disorders have different care pathways—general to highly specialised—depending on geographical location. A clear consensus on the most cost-effective and most valued treatment pathway is currently lacking. This study aimed to identify the most beneficial aspects of care through the perspectives of young people and their parents. We aimed to add depth to a parallel investigation of the cost-effectiveness of UK community-based eating disorder pathways. Methods: This qualitative study recruited participants and used online focus groups through Beat (Beating Eating Disorders, a UK National Charity). 19 young women aged 16–25 years with an existing or past eating disorder and 11 parents participated in four and two focus groups, respectively. The sample size was informed by saturation of themes. Data were analysed using thematic analysis. All participants provided written informed consent. The study was approved by the University of Exeter Medical School Research Ethics Committee. Findings: Focus group discussions showed that seven features were essential for a good level of care: professionals' knowledge of eating disorders and care pathways, and early provision of psychoeducation to young people and their families; a holistic approach balancing physical and psychological aspects of care from referral and early intervention to recovery and relapse prevention; early, rapid access to services including crisis and out-of-hours support; peer support for young people and support for family members; consistency and continuity, especially around interprofessional communication and transition from child to adult services; long-term view focusing on recovery and lifelong skills to facilitate relapse prevention; and an individually tailored, flexible approach. Interpretation: To our knowledge, this is the first exploration through online focus groups of patients' perspectives of UK-based eating disorder pathways. Our findings suggest that no existing pathway is more beneficial; rather, a cluster of features are perceived as essential for a good level of care across services. Although small, our study collated the views of both young people and parents from various geographical locations, and covered a wide range of health-care services. Funding: None.